Altered distributions of Ultrabithorax transcripts in extra sex combs mutant embryos of Drosophila. - Struhl, G.; Akam, M. (The EMBO Journal, 1985)
The product of the extra sex combs (esc) gene is required early in embryogenesis to ensure the correct spatial expression of the bithorax and Antennapedia gene complexes during subsequent development. Here we describe the spatial and temporal patterns of transcription of the Ultrabithorax (Ubx) gene in mutant esc embryos. In wild-type embryos, Ubx transcripts are first detected in the blastoderm primorida of particular thoracic and abdominal segments, predominately in a band of cells constituting the progenitor cells of parasegment 6: after gastrulation, high levels of transcript accumulate in a sharply restricted region of the germ band comprising parasegments 6-12. In esc- embryos, the initial pattern of Ubx transcripts appears indistinguishable from that of wild-type embryos. However, following gastrulation and germ band extension, Ubx transcripts accumulate in most of the ectodermal and mesodermal derivatives of the body, including those of all 14 parasegments. Then, the abundance of the transcripts declines so that after germ band shortening (12 h after fertilization), only low levels are detected in each parasegment. These results show that the esc gene product is not involved in choosing where the Ubx gene is to be expressed, but rather, that it acts subsequently to ensure that the gene remains off in those primordia in which it is not initially activated. In addition, they suggest the possibility that other homeotic genes may regulate Ubx expression --in this case, the accumulating products of other indiscriminately expressed homeotic genes serving to down-regulate Ubx transcription throughout the body.